Direct dotterising or angioplasty of acute stroke due to tandem atherosclerotic occlusions - Yeo, Leonard L. L.; Simonato, Davide; Bhogal, Pervinder; Gopinathan, Anil; Cunli, Yang; Ong, Samuel W. Q.; Jing, Mingxue; Tan, Benjamin Y. Q.; Sia, Ching-Hui; Jia, Tom; Cester, Giacomo; Gabrieli, Joseph-Domenico; et al. (Frontiers in Stroke, 2023)
Background Tandem occlusions cause 10–15% of LVO acute ischemic strokes but are difficult to treat endovascularly and frequently excluded from clinical trials. The optimum endovascular method is still debated, however going directly through the carotid occlusion can speed up the procedure and reduce procedural risk by eliminating an exchange maneuver. Method Using retrospective data from three centers, we compared treating atherosclerotic tandem occlusions using a 0.035'-guidewire and direct dotterisation or angioplasty with a peripheral vascular balloon suitable for the wire, vs. the usual technique of an 0.014'wire. We compared the successful recanalization (mTICI 2b-3) rates, 90 days' functional outcomes (mRS 0–2), and puncture-to-recanalization times between both procedures. Results Forty-two consecutive patients with atherosclerotic tandem occlusions were included; 25 were treated with the 0.014'wire technique and 17 with the 0.035'-guidewire and direct dotterisation or angioplasty with a peripheral vascular balloon technique. The direct technique achieved a higher rate of successful recanalization (100 vs. 72%, P = 0.018), better functional outcome (88.4 vs. 48.0%, P = 0.044), and faster procedure times (mean 65.1 mins vs. 114.8 mins, P < 0.001). The number of attempts was similar between both groups (median 2 vs 3 attempts, P = 0.101). There was no significant difference in the complication rate between both groups (5.9 vs. 12.0%, P = 0.462). Conclusion Compared to previous endovascular techniques for treating atherosclerotic tandem occlusions, the direct technique using standard 0.035' guidewires and dotterisation or a peripheral vascular balloon is significantly faster with better outcomes. However, this will require further external validation in larger cohorts.